Artificial Intelligence in Primary and Secondary Education: A Systematic Review - Dongjo Shin (Korea Society of Educational Studies in Mathematics, 2020)
Recently, the education system has been changing rapidly with the advent of the Fourth Industrial Revolution and the COVID-19 global pandemic. In this situation, this study reviewed 51 international research studies that used artificial intelligence in the context of primary and secondary education 2015-2020. The results of this study show that artificial intelligence was used most frequently in mathematics education and mainly for learning fractions and linear equation. Studies that used artificial intelligence in education were most likely to be conducted for elementary and middle school students, and quantitative methodology was mainly used to examine the impacts of artificial intelligence on students' achievement and affective domains. Systems that used artificial intelligence tended to be in the form of intelligent tutoring systems that provide step-by-step tutoring and adaptive, personalized feedback. In these systems, teachers tended to play minor roles, assisting the interaction between students and the artificial intelligence system.